Comparative study of power analysis attacks based on template and KNN algorithm - Jifang JIN; Chengyuan LIU; Xiaohong FAN; Xiaoyi DUAN; Jiayu LIU (Dianxin kexue)
Power analysis attack is still the most threatening type of side channel attack on cryptographic hardware.The template analysis attack with the attack of KNN algorithm was compared.Firstly, three dimensionality reduction methods of Pearson correlation coefficient, mutual information and maximum information coefficient and distance correlation coefficient were studied.Then, the effects of the number of feature points on the attack success rate of the two power analysis attacks under the same number of power consumption curves were compared.At the same time, the effects of different dimensionality reduction techniques on the two power analysis attacks when the number of power curves is the same and different.The results show that the template attack is better than the KNN algorithm attack in running speed, memory occupation and robustness, and the KNN algorithm attack has better performance in attack success rate.